(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
Nowadays every creative sector is seeing an increase in the use of intelligent software and mobile applications. The use of Artificial Intelligence (AI) in social and cultural sectors has been drastically increased in all over the world including India. Modern development of AI technology has shown that human beings are no longer indispensable for creative works. A machine equipped with AI technology can independently generate creative works where the use of human intelligence is very nominal. On the other hand, the protection of these AI generated works in terms of the Intellectual Property Rights (IPR) specifically the copyright is quite essential in the contemporary era. Although the relationship between copyright protection and AI is an emerging issue of the intellectual property law, it has received hardly any attention from the law and policy makers till date. Gradually, AI generates artworks that will significantly contributes to the cultural development of the country. However, the copyright law and implementation mechanism are yet to be well equipped to handle an upsurge in the production of AI-generated works. In light of the rapid advancement of AI, the identity of authorship may be often questioned and it could be a serious challenge to the Indian copyright laws as well. In this article, the authors have endeavored to sketch the future of copyright in the advancement of AI industry. Further, the authors suggest some desired contemporary changes to the existing legal regime in order to cope up with the future challenges of AI.